Is there a difference between solicited and unsolicited bank ratings and if so, why? - Patrick Van Roy (National Bank of Belgium, 2006)
This paper analyses the effect of soliciting a rating on the rating outcome of banks. Using a sample of Asian banks rated by Fitch Ratings ("Fitch"), I find evidence that unsolicited ratings tend to be lower than solicited ones, after accounting for differences in observed bank characteristics. This downward bias does not seem to be explained by the fact that betterquality banks selfselect into the solicited group. Rather, unsolicited ratings appear to be lower because they are based on public information. As a result, they tend to be more conservative than solicited ratings, which incorporate both public and nonpublic information.
Keywords: G15; G18; G21; 330; Credit rating agencies; Unsolicited ratings; Selfselection; Public disclosure; Accounting transparency; Kreditwürdigkeit; Bewertung; Bank; Schätzung; Asien